The Multifarious Role of Microglia in Brain Metastasis - Soto, Manuel Sarmiento; Sibson, Nicola R. (Frontiers in Cellular Neuroscience, 2018)
The immune landscape in brain metastasis is a very heterogeneous framework. Amongst a broad plethora of cells within the tumour microenvironment, the presence of activated microglia has been perfectly described. The innate role of microglial cells is to detect and eliminate any insults that may disturb the regular behavior of the brain. As part of its defensive role, it releases pro- and anti-inflammatory cytokines that aim to modulate the inflammatory scenario at the metastatic foci. However, the long-term effects that these cells may exert on the metastatic progression is not clear. One of the biggest challenges in the field is to distinguish between brain resident microglial cells and infiltrated bone-marrow derived macrophages. Part of this issue is the fact that both cell types share similar phenotypes. Current studies are based on the modulation of the immune response against cancer cells (immunotherapy). However, most of current clinical trials and newly developed drugs focus on the adaptive immune response (e.g. immune blockade check-points). Additionally, the unique structure of the central nervous system with the presence of the blood-brain barrier have hindered a significant advance in novel therapies against brain metastasis. In this manuscript, we describe current advances in characterization of tumour-associated microglia and macrophages, the importance of microglia during the anti-cancerous response, and the future direction for the development of new strategies against this complex disease.